HALITOSIS ASSESSMENT IN PATIENTS WITH ORTHODONTIC APPLIANCE AND THEIR ASSOCIATION WITH BULLYING - Mendes de Lima, Walkiria; de Almeira Lawal, Melaine; Novaes Vieira, Celi (Health and Society, 2022)
Halitosis is the term used to define the unpleasant odor exhaled through exhaled air, which may be signaling a pathological, physiological or adaptive condition. Most individuals who present this alteration experience personal discomfort, social embarrassment and emotional anguish, which can cause serious disturbances of coexistence, especially in the school environment. The etiology of halitosis is multifactorial, but its main cause comes from the formation of volatile sulfur compounds (VSC) resulting from the proteolytic bacterial action on stagnant organic matter in the oral cavity. The use of orthodontic appliances may be an agent related to the development of this alteration, since it favors the accumulation of organic residues, epithelial desquamation, gingival inflammation, in addition to making local hygiene difficult. Therefore, the present study aims to evaluate the breath of patients with orthodontic appliances and also the possible presence of bullying related to such an event, in young adults aged between 18 and 24 years, students at Universidade Paulista de Brasília. Breath assessment was performed using an organoleptic test (gold standard), which is performed by the examiner’s sense of smell, and a Halimeter® portable monitor, and saliva assessment was performed using a sialometry test, in which the amount of saliva was evaluated. The possible relationship with bullying was assessed through a specific questionnaire. Of the twelve students included in the study, seven presented halitosis when evaluated through the organoleptic test, however, of these seven only two presented parameters compatible with halitosis, when evaluated by the Halimeter®. In relation to bullying, this study showed that it was present in the lives of many respondents, but not necessarily because of breath.